Analisis Semiotika Ruang Tamu Rumah Panggung Masyarakat Bugis Baranti - M., Munarsi; Gamalia, Auditha Nurul; Salenda, H. (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2025)
This research examines the expression of space in the stilt houses of the Bugis community in Baranti District, focusing on the interior elements of the living room.The living room in the Bugis stilt house not only functions as a functional space but also serves as a medium to express the social status and cultural identity of the homeowners.This study uses a semiotic approach with Peirce's trichotomy theory to analyze the signs on the interior elements of the living room that reflect the social, cultural, and status symbols of the homeowners.The signs found are divided into two main categories, namely collective signs that reflect shared social values (such as religious symbols, pilgrimage status, and family identity) and individual signs that reflect the personal expression of the homeowner, influenced by aesthetic preferences and socio-economic background.The research results show that noble houses tend to retain traditional elements that have deep philosophical and cultural meanings, such as the use of Jepara carved chairs and family lineage documentation photos, which serve as symbols of high social status.On the other hand, the homes of ordinary people use interior elements to express social status achieved through personal accomplishments, such as collections of educational photos and collections of cups that indicate hajj status.